The roles of media in spreading awareness during covid-19 pandemic / Aini Nadhirah Ismail ... [et al.] - Ismail, Aini Nadhirah; Massury, Fatin Masyarah; Abdul Ghafor, Nurul Najihah; Ridzuan, Abdul Rauf; Sultan Mohideen, Rosilawati; Ilyas, Ilya Yasnoriza; Bakar, Mohd Hilmi (Faculty of Communication & Media Studies, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) has created a global health crisis that has had a deep impact on the way we perceive our world and our everyday lives. Today, social media such as Twitter, Facebook and Instagram, have become primary sources of information. They are also vehicles for fake news and disinformation. During a crisis like the COVID-19 pandemic, media takes the roles in spreading awareness during Covid-19 pandemic to ensure the society aware about this disease. For the methodology of this research, the researchers follow the research design of qualitative research. The researchers uses semi-structured interview in gathering information from the informants. At the end, the researchers found out that media plays a big roles in spreading awareness during covid-19 pandemic. People might see that media can be the effective way in spreading awareness during covid-19 pandemic, but certain people might see that media will bring the negative impact to the society. Also in taking roles as media during this pandemic, they need to identify and analyze the best content to be shown to the target audience.